Distributed humanitarianism: Volunteerism and aid to refugees during the Russian invasion of Ukraine. (24th January 2023) - Cullen Dunn, Elizabeth; Kaliszewska, Iwona
Abstract: When Russia invaded Ukraine in 2022, the world's largest humanitarian aid agencies were largely nowhere to be seen. In their absence, tens of thousands of volunteers from Ukraine, Poland, and further abroad helped the more than 16 million displaced and war‐affected Ukrainians. This massive volunteer response represents a case of "distributed humanitarianism, " a post‐Fordist form of humanitarian aid that disrupts the Fordist international aid industry that has existed since the end of World War II. Because it uses donated money, labor, and goods; avoids bureaucratic accountability measures; and relies on person‐to‐person aid chains, distributed humanitarianism is faster, more cost‐efficient, and more resilient than large‐scale institutionalized aid.